Influence of a Z(+) (1540) resonance on K+N scattering - Haidenbauer, J.; Krein, G. (Amer Physical Soc, 2003)
The impact of a (I=0, J(P)=1/2(+))Z(+) (1540) resonance with a width of 5 MeV or more on the K+N(I=0) elastic cross section and on the P-01 phase shift is examined within the KN meson-exchange model of the JUlich group. It is shown that the rather strong enhancement of the cross section caused by the presence of a Z(+) with the above properties is not compatible with the existing empirical information on KN scattering. Only a much narrower Z(+) state could be reconciled with the existing data-or, alternatively, the Z(+) state must lie at an energy much closer to the KN threshold.